2010
DOI: 10.1111/j.1469-0691.2009.03008.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Moraxella catarrhalis colonization in healthy Dutch children during the first 14 months of life

Abstract: Moraxella catarrhalis is an established bacterial pathogen, previously thought to be an innocent commensal of the respiratory tract of children and adults. The objective of this study was to identify significant risk factors associated with M. catarrhalis colonization in the first year of life in healthy Dutch children. This study investigated a target cohort group of 1079 children forming part of the Generation R Study, a population-based prospective cohort study following children from fetal life until young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…Observations of parent-child interaction and behaviour, such as executive function, heart rate variability, infant-parent attachment, moral development, and compliance with mother and child have been performed at the ages of 14, 36 and 48 months and with father and child at the age of 48 months [240,241]. Biological materials have been collected, including bacterial colonization measured by nasal-and nasopharyngeal swabs at the ages of 1.5, 6, 14 and 24 months, cortisol day rhythm measured by repeated salivary samples at the age of 14 months and, if parents give consent, blood samples at the ages of 6, 14 and 24 months [242][243][244][245][246][247][248][249][250][251].…”
Section: Questionnairesmentioning
confidence: 99%
“…Observations of parent-child interaction and behaviour, such as executive function, heart rate variability, infant-parent attachment, moral development, and compliance with mother and child have been performed at the ages of 14, 36 and 48 months and with father and child at the age of 48 months [240,241]. Biological materials have been collected, including bacterial colonization measured by nasal-and nasopharyngeal swabs at the ages of 1.5, 6, 14 and 24 months, cortisol day rhythm measured by repeated salivary samples at the age of 14 months and, if parents give consent, blood samples at the ages of 6, 14 and 24 months [242][243][244][245][246][247][248][249][250][251].…”
Section: Questionnairesmentioning
confidence: 99%
“…With respect to M. catarrhalis, it has been shown that many factors affect nasopharyngeal carriage of this human-specific pathogen, including, for example, the presence of siblings, day care attendance and respiratory illness (Faden et al, 1997;Hendley et al, 2005;Peerbooms et al, 2002;Principi et al, 1999;Verhaegh et al, 2010). Furthermore, there is increasing information regarding the biological mechanisms facilitating M. catarrhalis-mediated colonization and disease development, with most publications stressing the importance of bacterial adherence as an essential first step in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the bacterium rapidly colonizes the nasopharynx soon after birth and that the carriage rate of M. catarrhalis in healthy children varies between 7 and 36 % (Verhaegh et al, 2010). However, in children with upper respiratory tract infections (URTI), including acute otitis media (AOM), the carriage rate increases to approximately 50 % (Berner et al, 1996;Konno et al, 2006;Pettigrew et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Japanese study conducted in 1999, children aged 1 month to 5 years attending day-care centers, 35% were found to be colonized [3]. In The Netherlands, a comparative study of 1.5 to 14 month old children born between February 2003 and August 2005, indicated a carriage rate for children ranging from 11.8% at the age of 1.5 months to 29.9% at the age of 6 months and 29.7% at the age of 14 months [4]. In general, despite local geographical variation, infants tend to become colonized with M. catarrhalis at a very early age, resulting in a nasopharyngeal colonization peak for M. catarrhalis at 2 years of age [5].…”
Section: Introductionmentioning
confidence: 99%